Case Report: Two years of compassionate use with Olipudase-alfa in a child with neurovisceral acid sphingomyelinase deficiency - Deodato, Federica; Boenzi, Sara; Greco, Benedetta; Graziosi, Alessia; Dionisi-Vici, Carlo (Frontiers in Pediatrics, 2025)
Acid sphingomyelinase deficiency (ASMD) is a rare, progressive lysosomal storage disorder resulting from a deficiency in acid sphingomyelinase, leading to sphingomyelin accumulation and multi-organ damage. ASMD presents a broad phenotypic spectrum with a continuum of severity, making it challenging to predict the phenotype in very young children and differentiate between acute and chronic neurovisceral disease. No disease-specific treatments existed for ASMD. Recently, Olipudase-alfa, an intravenous enzyme replacement therapy, has been approved for non-neurological manifestations based on clinical trial results showing significant improvements. This report details the compassionate use of Olipudase-alfa in a 8-month-old boy. At baseline, he exhibited hepatosplenomegaly, elevated transaminases, and normal developmental milestones, consistent with a chronic neurovisceral phenotype. The treatment commenced at 8 months of age, escalating from 0.03 mg/kg to 3 mg/kg bi-weekly. Throughout the two-year period, the child tolerated the therapy well, with no severe adverse events reported. Notable clinical outcomes included a significant reduction in spleen and liver size, normalization of liver function tests, and stabilization of the lipid profile. The biomarker Lyso-sphingomyelin significantly reduced but never normalized, while oxysterols completely normalized. In the following months, the patient exhibited neurocognitive regression, allowing to define an acute neurovisceral phenotype. Although not impacting on the neurological manifestations, treatment with Olipudase-alfa strikingly improved the child's visceral symptoms, contrasting with the typical progressive decline seen in untreated patients. This report highlights the importance of early intervention, even in patients with neurovisceral phenotypes, as it can enhance quality of life for both patients and their families. Our findings advocate for reconsidering treatment eligibility criteria based solely on clinical phenotype definitions, highlighting the need for a tailored approach in ASMD management.